Effects of Bacterial Infection on Airway Antimicrobial Peptides and Proteins in COPD - Parameswaran, Ganapathi Iyer (American College of Chest Physicians, 2011)
BACKGROUND: Pathogenic bacteria colonize the airways of 30% to 40% of patients with COPD and cause approximately 50% of exacerbations. New strains of nontypeable Haemophilus influenzae (NTHI) and Moraxella catarrhalis are associated with exacerbations. Antimicrobial protein/peptides (AMPs) play important roles in innate lung defense against pathogens. To our knowledge, the changes in AMP baseline levels in respiratory secretions during bacterial colonization and exacerbation have not been described. The objective of this study was to elucidate the effects of the acquisition of a new strain of pathogenic bacteria on the airway levels of AMPs in patients with COPD. METHODS: One hundred fifty-three samples from 11 patients were selected from COPD sputum samples collected prospectively over 6 years. Samples were grouped as culture-negative (no pathogenic bacteria), colonization, and exacerbation due to new strains of NTHI and M catarrhalis. Levels of lysozyme, lactoferrin, LL-37, and secretory leukocyte protease inhibitor (SLPI) were measured by enzyme-linked immunosorbent assay and compared among groups by paired analysis. RESULTS: Compared with baseline, sputum lysozyme levels were significantly lower during colonization and exacerbation by NTHI (P = .001 and P = .013, respectively) and M catarrhalis (P = .007 and P = .018, respectively); SLPI levels were lower with exacerbation due to NTHI and M catarrhalis (P = .002 and P = .004, respectively), and during colonization by M catarrhalis (P = 032). Lactoferrin levels did not change significantly; LL-37 levels were higher during exacerbation by NTHI and M catarrhalis (P = .001 and P = .018, respectively). CONCLUSIONS: Acquisition of NTHI and M catarrhalis is associated with significant changes in airway levels of AMPs, with larger changes in exacerbation. Airway AMP levels are likely to be important in pathogen clearance and clinical outcomes of infection in COPD.